"You Can Say I Got Desensitized to It": How Men of Color Cope with Everyday Racism in Online Gaming. (August 2019) - Ortiz, Stephanie M.
Online trolling as a form of overt racism forces sociologists to reexamine contemporary understandings of racialization in a color-blind era. In this article, I demonstrate how men of color construct meanings about their experiences of racist hate speech, referred to as trash talk, on an online gaming platform. Analyzing semistructured interviews, I show that respondents cope with this form of racism through a process of desensitization. This strategy is mediated by respondents' peer socialization on how to effectively manage this racism as men, and their stigmatization by others who do not view these experiences as "real" racism. Strategies to cope with racism in this domain are thus gendered in ways that encourage men of color to remain silent in the face of repeated hate speech. This study further demonstrates how individual strategies developed to navigate racism online are tied to broader, collective understandings of the meanings of race, racisms, and masculinity.